The Role of Intelligence Quotient as a Risk Factor for Depression: A Literature Review - Bella Sagita Pratiwi (Scientia Psychiatrica, 2021)
Depression is a mood disorder with general characteristics in the form of changes in sleep patterns and appetite, psychomotor disorders, concentration problems, anhedonia, fatigue, hopelessness and helplessness, and suicidal ideation. If the depressive disorder goes on for a long time (dysthymia), the person is suggested to be moody, lazy, or withdrawn from relationships because he loses interest in almost all aspects of his life. Depression is a psychiatric disorder that is often found with a prevalence of around 15%. In general, the onset of major depressive disorders is at the age of 20 to 50 years, but the most often is at the age of 40 years. Cognitive plays a role in the aetiology and prognosis of someone with depression. The higher the cognitive level of a person, the more it will affect the cure rate and prevent recurrence in someone experiencing psychiatric disorders. This literature review will explain the role of intelligence quotient in depressive disorders.